The Design and Build A Field Tennis Robot With Wifi Based Hand Gesture Recognition Using PID Method - Roziqin, Mohamad Fatkhan; Joni, Koko; Ulum, Miftachul (Jurnal Sistem Telekomunikasi Elektronika Sistem Kontrol Power Sistem dan Komputer, 2021)
In the modern era, the world of technology is developing rapidly, especially in the field of robotics. In the field of robot industry has begun to be widely used to help ease human work. In the field of sports the use of robots has begun to develop but is limited to mere entertainment and will lack benefits. From the problems above, this final project will create a robot tennis ball taker design with wifi-based hand gesture control using the PID method. In use, this robot will be used to grab the ball by using the Accelerometer Sensor. This sensor can measure the slope of an object because it has 3 axes namely X, Y, and Z by tilting the sensor towards the front, back, sideways right and left side and wifi as a data transfer communication. In synchronizing the motor so that the robot can move stable and smooth, the PID control method is used so that the movement of the motor when turning or maneuvering becomes smooth and stable.